Distribusi dan Luas Stomata pada Tanaman Hias Monokotil - Ersa Oktaviani; Entin Daningsih (Jurnal Ilmu Pertanian Indonesia, 2022)
Ornamental plants give beauty to the surrounding environment. Fresh air is created around the plant. It is concerned with transpiration which relates to the distribution and extent of stomata. The study measured the distribution and extent of stomata in monocot plants used as houseplants. The experimental design used a complete randomized design (RAL) factorial with five replications. The main factors were six types of monocot plants and three parts of plants (top, middle, and bottom). The interaction between plant types and parts was a combination factor. The distribution and area of the stomata were measured using replica methods and micrometers. The data was analyzed using the factorial RAL model statistical analysis system and followed up with the smallest real different test for significant treatment. The distribution of stomata was correlated with the stomata area to observe the relationship between the two. Plant types, plant parts, and combinations of both have a noticeable effect on the stomata distribution and area. The Paris lilies (Chlorophytum comosum (Thumb) Jacq.) have the highest stomata distribution (20.53%) compared to others, with a stomata area of 291.89 μm2. Meanwhile, the top part of the plant has the highest distribution and differs from the middle and bottom. The highest stomata distribution is at the top of the plant (15.02%) and lowest at the bottom (11.96%), while the smallest stomata area is at the top of the plant (687.62 μm2) and the widest is at the bottom (813.88 μm2). The stomata distribution correlates inversely with the stomata area of both plant types, plant parts, and a combination of both. Keywords: ornamental plants, monocotyledon, stomatal area, stomatal distribution